OBJECTâS MOVEMENT SIMULATION WITH AIR DRAG: AERODYNAMICS WALL AND KNUCKLEâS EFFECT - Tohari, Daniel
The drag force of air on an object can be analyzed using the Stokes or Quadratic concept (often referred to as the Newtonian method). The drag force considered in this study is a Newtonian model that is numerically constructed in Python using a 4th order Runge-Kutta integrator. The integrator solves the acceleration function experienced by the object when subjected to a drag force as a function of position. The motion of the object affected by the drag force is given a variation in the drag coefficient, which gives a variation in the position of the aerodynamic wall, the condition when the object moves vertically downward. The motion of objects affected by drag in one state will also experience a lifting force, due to the angle of rotation orientation on the object. The motion of objects affected by these two forces can be modeled as a knuckle motion. The results obtained from the numerical solution of the two conditions of the object are then presented in the form of a simple application in the form of a GUI, so that users can easily operate the simulation of objects. This research is expected to be a solution for students in understanding the motion of objects affected by drag forces that occur when taking classical mechanics courses.